Role of Diagnostic Hysterolaparoscopy in Evaluation of Female Infertility at the National Center for Diagnosis and Treatment of Infertility-al Jabal AL Akhdar - Ramzi Mohamed, (AlQalam Journal of Medical and Applied Sciences, 2026)
Infertility, affecting 10–15% of reproductive-age couples, has emerged as a pressing medical and social challenge. This cross-sectional study evaluated the diagnostic value of hysterolaparoscopy (HL) in the assessment of female infertility at the National Center for Diagnosis and Treatment of Infertility, Al Jabal Al Akhdar. This is a prospective interventional study that enrolled 165 women with a history of primary or secondary infertility at national center for Diagnosis and Treatment of Infertility-AL Jabal AL Akhdar in the period from July 2025 to Dec 2025. Those with a history of active pelvic infection or contraindication of anesthesia were excluded. Of the 165 women evaluated, 91 (55.15%) were diagnosed with primary infertility. Laparoscopic examination identified abnormalities in 49.09% of cases, with tubal obstruction (18.79%), peritubal adhesions (12.37%), and endometriosis (11.52%) being the most prevalent findings. Hysteroscopic assessment most commonly revealed endometrial polyps as the leading intrauterine abnormality. Diagnostic HL is an effective, safe diagnostic tool when performed by experienced hands for diagnosing and treating pelvic pathologies, such as adnexal adhesions, endometriosis, and uterine septum, which are usually missed by other diagnostic modalities.